Personal hygiene habits of Filipino male adolescents - Temporal, Marie Celine Navarrete; Malicdem, Eleanor A. (2008.)
The study investigated the personal hygiene habits of Filipino male adolescents. Survey was conducted to identify the major practices done by male adolescents to keep body cleanliness, good grooming and personal hygiene. Subjects were 45 male adolescents selected bu cluster sampling from one (1) private and one (1) public school in Quezon City. The respondents were between the ages of 14 and 16 years. Data is presented and analyzed through descriptive statistics. Findings show that among the 18 given practices, only seven (7) were identified to be similar among Filipino male adolescents. These personal hygiene habits are brushing of teeth thrice a day (53%0, use of deodorant once a day (76%), use of shampoo once a day (51%), wiping of toes once a day (51%), cleaning and cutting of nails once a week (64%), use of handkerchief once a day (71%), and cutting of hair once a month (71%). Top sources of information and major influences were identified among a set of variables provided. Respondents ranked the variables according to its authority over their decisions pertaining to personal hygiene such as the source of information they relied on for the purchase and use of personal hygiene products, and the styles of grooming. Based on the findings, the family is the primary source of information and major influence on the purchase and use of hygienic products for Filipino male adolescents. They also consult doctor/s or people from the medical profession, peers, and teachers. The television is the top medium referred to by the male adolescents for information and influence on personal hygiene. On good grooming, Filipino male adolescents turn to family and friends for their top influences. Celebrities who are looked up to as role models are also one of the top influences on grooming.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: Hygiene -- Philippines; Teenagers -- Philippines -- Hygiene